ANALISIS PELATIHAN, MOTIVASI, DAN KETERAMPILAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PABRIK ROKOK SIMUSTIKA KABUPATEN TULUNGAGUNG - Sari, Risqi Puspita (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The reason for this research is to experimentally investigate the impact of job training, motivation and skills on the efficiency of representatives at Simustika Cigarette Factory Tulungagung. This study uses a quantitative methodology with a causal relationship investigation procedure. The information inquiry procedure uses several direct fallbacks. Information research with clear fact finding, traditional assumption test, speculation test and synchronous test. The consequences of the t-test show (1) the importance level of 0.046 < 0.05 implies that work preparation basically affects the representative efficiency, (2) the 0.025 < 0.05 level of importance implies that work inspiration has a fundamental influence on the representative efficiency, (3) The importance level of 0.022 < 0.05 implies that work skills have a fundamental influence on employee efficiency, (4) and the level of importance of 0.00 < 0.05 implies that work preparation, inspiration and work skills have basically affected the efficiency of workers.